2020
DOI: 10.3390/ijerph17228618
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Coaching Behavior and Athlete Burnout: Mediating Effects of Communication and the Coach–Athlete Relationship

Abstract: The purpose of this study was to investigate the relationships between perceived coaching behavior (autonomy-supportive and controlling), communication, coach–athlete relationship, and athlete burnout. The study participants comprised 347 Korean active collegiate athletes from 10 sports. The results of the final model indicated that autonomy-supportive coaching was positively related to communication, whereas controlling coaching was negatively related to communication. Communication was positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Thus, the process of reliability analysis is crucial and determinant for instrument quality. The present results provide reliability of the instruments and thus can be used as measures of coaching behavior, that is concurrently associated with players and team performance (Choi et al, 2020). In this sense, the coach needs to think about the best communication strategies to maximize the players' performance during competition (Kim and Park, 2020) and afterward have the ability to reflect on their behavior during the competitive moments.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, the process of reliability analysis is crucial and determinant for instrument quality. The present results provide reliability of the instruments and thus can be used as measures of coaching behavior, that is concurrently associated with players and team performance (Choi et al, 2020). In this sense, the coach needs to think about the best communication strategies to maximize the players' performance during competition (Kim and Park, 2020) and afterward have the ability to reflect on their behavior during the competitive moments.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, they decisively contribute to the technical, tactical, physical, and psychological aspects of the players and the team overall during competition (Pesca et al, 2017). The coach-athlete relationship is a crucial aspect of the coaching process and the coaching type adopted by the coaches is capable of influencing expected results (Choi et al, 2020). Specifically, how coaches prepare working strategies and how the team is oriented from a technical point-of-view is determinant of increased athlete and team confidence and performance (Almeida et al, 2019;Keatlholetswe and Malete, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes who showed their coaches as trainers and more democratic behaviors and more authoritarian behaviors were less tired. Findings of Choi et al's (2020) study on the relationship between coaching behaviors and job burnout with the mediating role of athlete-coach relationship and relationship showed that our current understanding increases the relationship between perceived coaching behavior and athletes' burnout and important roles Clarifies team relationships and the coach-athlete relationship (Choi et al, 2020). The results also showed that autonomy-supportive coaching behaviors have a negative relationship with burnout and coaching control has a positive and significant relationship with job burnout.…”
Section: Introductionmentioning
confidence: 80%
“…Harmoniously, sports also provide a welcome break from the humdrum of daily life for students. On the other hand, study findings found that coaches' commitment can affect student-athletes (Abo s et al, 2021;Choi et al, 2020;O'Neil & Hodge, 2020). Student-athletes were also highly connected to their coach in every training session and competition.…”
Section: Coach and Student-athletesmentioning
confidence: 99%